Charting Relations between Intersectionality Theory and the Neurodiversity Paradigm - Strand, Lauren Rose (Disability Studies Quarterly, 2017)
This essay explores central elements and applications of intersectionality theory and the neurodiversity paradigm. First, the histories and tenets of intersectionality theory and neurodiversity paradigm are provided. Then, areas are explored where each of the two approaches might further engage with the principles of the other. Finally, the essay concludes by broadly considering the efforts made by the Black Lives Matter movement and the Autistic Self Advocacy Network to bring attention to and end police violence as both networks employ and attend to elements of intersectionality and neurodiversity. The way these two networks draw on both intersectionality and neurodiversity to further their mission could be a possible site for scholars to consider in the interest of advancing dialogues between intersectionality theory and the neurodiversity paradigm. Ultimately, the essay calls for a continued exploration of the potentials for intersectionality and neurodiversity to complement and complicate one another, both in terms of theoretical development and coalition building.